Pro jQuery Mobile - Broulik, Brad.; SpringerLink (Online service) (Berkeley, CA : Apress, 2011)
You need to build an app, and you need it to run everywhere. And you need it now! jQuery Mobile gives you the ability to write once and run everywhere using jQuery and jQuery UI. Pro jQuery Mobile will teach you how to create themable, responsive, native-looking applications for iOS, Android, Windows Phone, Blackberry, and more. Discover what sets jQuery Mobile apart from other mobile web development platforms Walk through practical examples of jQuery Mobile features, including design elements and event handling Dig into the jQuery API, integrate web services, and learn how to publish to app stores with Phone Gap jQuery Mobile is a framework for delivering cross-platform mobile web applications with a unified interface. jQuery Mobile combines responsive layouts with progressive enhancement to render the best possible user experience from a single code base. With Pro jQuery Mobile, you'll be creating amazing mobile apps in no time.
Keywords: Computer science; Computer Science; Computer Science, general